Patient-Experience of Trapeziectomy for Trapeziometacarpal Osteoarthritis in Wide-Awake Local Anesthesia no Tourniquet, 2-Year Follow-up - Reiser, D; Brandt, V; Sagerfors, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: The purpose of this study was to assess the patient experience of trapeziectomy under WALANT for trapeziometacarpal joint (TMJ) osteoarthritis (OA) in a prospective study with 2-year follow-up. MATERIAL AND METHODS: The study included 23 patients with TMJ OA undergoing trapeziectomy with WALANT. All patients were seen by a hand therapist preoperatively and at 3, 12, and 24 months postoperatively. At each visit, VAS pain scores, thumb range of motion, grip strength, and Disabilities of the Arm, Shoulder and Hand (DASH) score were assessed. The Picker Patient Experience (PPE-15) questionnaire was administered within 2 weeks of surgery. RESULTS: All 23 patients completed the PPE-15 questionnaire. Their mean age was 64 years. The 21 patients who remained at the 24-month follow-up all said they would choose the same anaesthesia method again. At this follow-up, VAS pain scores, thumb range of motion, key pinch grip and DASH scores had improved significantly, while thumb opposition and hand grip strength remained largely unchanged. The majority of patients felt well informed before and during the procedure, and all patients rated pain relief as good or satisfactory. Nearly 40% of patients reported receiving inadequate information about the postoperative medications. DISCUSSION: Patients have a positive attitude to trapeziectomy with WALANT, and seem to prefer WALANT over other methods of anaesthesia. Trapeziectomy with WALANT for TMJ OA is a safe procedure and appears to give a functional outcome similar to trapeziectomy under general anaesthesia. CONCLUSIONS: Trapeziectomy with WALANT for TMJ OA is safe, preferred by patients and has similar clinical outcome as trapeziectomy in general anesthesia. KEY WORDS: trapeziectomy, osteoarthritis, WALANT.
Keywords: síla ruky; spokojenost pacientů; Metacarpal Bones; Carpometacarpal Joints; Hand Strength; průzkumy a dotazníky; Female; osteoartróza; Pain Measurement; palec ruky; Patient Satisfaction; výsledek terapie; ženské pohlaví; karpometakarpální klouby; Surveys and Questionnaires; metakarpální kosti; lidé; Treatment Outcome; následné studie; Thumb; měření bolesti; Range of Motion, Articular; rozsah kloubních pohybů; prospektivní studie; Follow-Up Studies; Male; Trapezium Bone; Prospective Studies; Aged; lokální anestezie; Osteoarthritis; Anesthesia, Local; lidé středního věku; trapézová kost; mužské pohlaví; senioři; Middle Aged; Humans